The Effect of Culture System on Benzaldehyde Biotransformation by Cultured Cells of Silybum marianum (L.) Gaertn.: Benzaldehyde biotransformation - Asghari, Gholamreza; Mahmudi, Shohreh (Iranian Journal of Pharmaceutical Sciences, 2005)
The abilities of Silybum marianum cell culture to biotransform benzaldehyde to benzyl alcohol in three culture systems were compared. Callus cultures of Silybum marianum were established from seedlings, and healthy suspensions and immobilized cultures grown on the Murashige and Skoog medium. S. marianum cells were immobilized in both agar beads and fiber cotton matrixes. Benzaldehyde was fed to S. marianum cell suspension and immobilized cultures. Biotransformation reactions were detected over 24 hours of incubation. The cultures then were extracted with dichloromethane and the extracts were subjected to GC and GC-MS analysis. The S. marianum culture systems exhibit different conversion rates in the reduction of benzaldehyde. Immobilization seemed to have an effect on the secondary metabolism, the cells immobilized in fiber cotton matrix were more efficient at performing the reduction process than both the freely suspended and agar immobilized cells. The ability of cultured plant cells to biotransform substrate appears to be dependent on the type of the culture system.